Antibacterial potential of Saussurea obvallata petroleum ether extract: A spiritually revered medicinal plant - Mishra, Abhay P; Saklani, Sarla; Sharifi-Rad, Mehdi; Iriti, Marcello; Salehi, Bahare; Maurya, Vineet Kumar; Rauf, Abdur; Milella, Luigi; Rajabi, Sadegh; Baghalpour, Navid; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2018)
Uttarakhand Himalayan region holds Asteraceae or Compositae as the largest family of flowering, medicinal and aromatic plants. Species belonging to this family rises from low altitude to the alpine region. Among Asteraceae, Saussurea obvallata (DC.) Edgew. is widely used in several indigenous systems of medicine. Flowers, leaves and rhizomes of S. obvallata are used for several traditional, religious, therapeutic and ornamental purposes. Aim of this study was to determine the chemical composition and antibacterial efficacy of petroleum ether extract (PEE) of S. obvallata. Gas chromatography-mass spectrometry (GC-MS) analysis was used for identifying phytochemicals present in the plant extract. Furthermore, the PEE was assessed for in-vitro antibacterial activity against selected Gram positive and negative strains. Structure of squalene and Î±-linolenic acid methyl ester were identified in PEE by GC-MS analysis, by comparing the results obtained with NIST library and literature reports. PEE exhibited significant activity against Staphylococcus aureus, Escherichia coli, Bacillus cereus, Bacillus subtilis with IC50 value of 87.2 ± 1.6, 98.4 ± 1.1 and 90.2 ± 1.8 µg/ml, respectively. These results showed that squalene and Î±-linolenic acid derivative identified in S. obvallata may be responsible for the observed antibacterial activity. To the best of our knowledge, this is the first report focused on the chemical composition and antibacterial activity of S. obvallata.